(untitled) (Revista Brasileira de Contabilidade e Gestão, 2023)
Objective: Given the context of adaptations in the public sector to managerial public administration, this research aims to investigate the influence of cognitive factors on the judgment of utility and acceptance of the cost information system (CIS) applied to the public sector. Method: This is a descriptive research, carried out from a single entity survey, with a quantitative approach to the data. The entity chosen for analysis was the State Treasury of the state of Rio Grande do Sul (RS) due to the progress made by RS in the implementation of the Cost Information System (CIS). For analysis of the collected data, path analysis was used. It was noticed in the analyzed case that the cognitive factors influence the judgment of utility and the acceptance of the new Cost Information System. Result: Most individuals have cognitive consonance with the Cost Information System, diminishing resistance to the implementation of the new system. Contributions: Cognitive perspectives in the implementation of management control systems in the public sector (especially CIS) and the varying acceptance of managers and civil servants in front of new management control systems can be added to the specialized literature. In addition to advancing the literature, this research can contribute to managers and civil servants to understand that the consonance among cognitive factors can mitigate processes of resistance to change and support the implementation of new management control systems.